Using Aromatherapy Candles from Coffee Bean Grounds to Reduce Anxiety at Work Post-Pandemic - Alif Gita Arumsari; Teguh Ardiansyah; Petrus Junake Ginting (PT FORMOSA CENDEKIA GLOBAL, 2023)
The COVID-19 pandemic has significantly increased anxiety levels in the workplace. This research explores the potential of using aromatherapy candles made from coffee bean grounds as an effective way to reduce post-pandemic anxiety. In this experiment, the test panel was given aromatherapy candles using the Organoleptic, Aroma Durability, Burn Time and Hedonic Test Methods. The results showed that the use of coffee bean aromatherapy candles resulted in a significant reduction in the anxiety levels of the test panel. Aromatherapy candles made from coffee bean dregs have proven effective in reducing anxiety levels while working post-pandemic. This product has the potential to be a useful tool in improving mental wellbeing in the work environment and providing a positive experience for users